Differential response of bacterial diversity and community composition to different tree ages of pomelo under red and paddy soils - Zheng, Chaoyuan; Kong, Kunpeng; Zhang, Yi; Yang, Wenhao; Wu, Liangquan; Munir, Muhammad Zeeshan; Ji, Baoming; Muneer, Muhammad Atif (Frontiers in Microbiology, 2022)
Rhizosphere soil microbial communities have substainal impact on plant growth by regulating the nutrients cycling. However, the dynamic changes in soil microbiota under different tree ages have received little attention. In this study, changes in soil physicochemical properties, as well as bacterial diversity and community structures (by high-throughput illumina MiSeq sequencing) were explored in pomelo tree of different ages (i.e., 10, 20, and 30 years old) under the red and paddy soils cultivated by famers with high fertilizer input. Moreover, the soil factors were also investigated that shape the bacterial community, such as soil pH, AP (available-phosphorous), AK (available-potassium), and AN (available-nitrogen). Results showed that pH significantly decreased, while AP, AK, and AN increased with increasing tree age under red soil. For paddy soil, pH was not changed, while AP was significantly lower under 10 year, and AK and AN contents were minimum under 30 year pomelo trees. Both soil types were dominated by Proteobacteria, Acidobacteria, Actinobacteria and showed contrasting patterns of relative abundance under different age groups. Bacterial richness and diversity decreased with increasing tree age in both soil types. Overall, bacterial community composition was different under different tree ages. RDA analysis showed that soil pH, AP, AK in red soil, while pH and AP in paddy soil showed most significant effect in changing the baterial community structure. Random forest model showed that Sinomonas and Streptacidiphilus in red soil and Actinoallomurus and Microbacterium in paddy soil were most important genera explaining the differences among different age groups. Co-occurrence network revealed that bacterial species formed a complex network structure with increasing tree age indicating more stable microbial association under 20 and 30 years compared to 10 years pomelo trees. Hence, contrasting patterns of changes in soil physicochemical proprties and soil microbial communities were recorded under different tree ages, and found that tree ages have significant effect on bacterial communutiy structure and richness.